Integration of Sustainable Development Goals (SDGs) Principles in the Independent Curriculum: An Exploratory Study of Best Practices and Challenges in Driving Schools - Nisak, Sayida Khoiratun; Puspitasari, Ratna; Hakim, Moch Lukman; Hanafiah, Hanafiah; Nugroho, Feby Arief (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to explore the integration of Sustainable Development Goals (SDGs) principles in the implementation of the Independent Curriculum at Indonesian Schools for Change. Using a qualitative approach with an exploratory case study method, this study involved 18 informants from five Schools for Change, consisting of principals, teacher leaders, class teachers, curriculum coordinators, and representatives of parents/school committees. Data collection techniques were carried out through in-depth interviews, participant observation, and document analysis. The results show that the integration of SDGs in the Independent Curriculum can be implemented through three main strategies: integrated learning in subjects, the Pancasila Student Profile Strengthening Project (P5), and school-community collaboration. Best practices found include a sustainable literacy park program, a renewable energy project, and an environmentally friendly school cooperative that effectively develop students' sustainability awareness. However, implementation faces significant challenges in the form of limited teacher understanding (89%), a lack of technological resources (72%), and cultural resistance to change (78%). This study concludes that although the Independent Curriculum provides flexibility to integrate SDGs values, it requires strengthening teacher capacity, providing adequate resources, and sustainable policy support to achieve optimal implementation.